2006
DOI: 10.1590/s0100-69162006000100014
|View full text |Cite
|
Sign up to set email alerts
|

Demanda energética de uma semeadora-adubadora para soja sob diferentes velocidades de deslocamento e coberturas do solo

Abstract: RESUMO:O objetivo deste trabalho foi avaliar a demanda energética requerida por uma semeadoraadubadora disponível comercialmente para plantio direto, submetida a quatro velocidades de deslocamento e três condições de cobertura do solo na implantação da cultura da soja. O experimento foi conduzido no Sítio Cazarotto, localizado no Distrito de Iguatemi, município de Maringá -PR, em Latossolo Vermelho distrófico. Utilizou-se de delineamento de blocos ao acaso, em arranjo de parcelas subdivididas, em que os tratam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 3 publications
1
4
0
3
Order By: Relevance
“…Given this behavior, this study is in agreement with the tendencies found by Bortolotto et al (2006), that when analyzing the power required on the drawbar for a seeder with four displacement speeds in different vegetation cover, observed that the coverage condition with spontaneous vegetation was the one with higher power requirement while the desiccated and rolled oat did not differ between themselves.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Given this behavior, this study is in agreement with the tendencies found by Bortolotto et al (2006), that when analyzing the power required on the drawbar for a seeder with four displacement speeds in different vegetation cover, observed that the coverage condition with spontaneous vegetation was the one with higher power requirement while the desiccated and rolled oat did not differ between themselves.…”
supporting
confidence: 91%
“…Siqueira et al (2013) characterized different Diesel fuel oil mixtures and reused soybean oil and evaluated the performance, on draw bar, of an agricultural tractor of tires and concluded that traction force increased as long as the enhance of operation speed. Bortolotto et al (2006) evaluated a seederfertilizer combine in four speeds and three vegetation covers and observed the increase of the traction force required by mechanized set due to increased speeds. Figure 6 shows power behavior due rotation and displacement speed in fertilization operation.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, Bortolotto et al (2006) found 2.5% increase in drawbar draft when the operating speed increased from 4.7 to 7.2 km h -1 , in a notill system in an Oxisol. But, Modolo et al (2004), Trintin et al (2005) and Furlani et al (2005) found no effects of increased operating speed on average values of drawbar draft.…”
Section: Drawbar Draft Requirementmentioning
confidence: 80%
“…However it was established that this operation requires more energy than seeding, since the results obtained for almost all equipment tested are superior to those obtained by BORTOLOTTO et al (2006), working with soybean seeding, and found demand of approximately 15 kWh ha -1 . .…”
Section: It Is Observed Inmentioning
confidence: 86%